NEW NOUNS AND NEW MEANINGS: THE SEMANTIC DYNAMICS OF NON-STANDARD ONLINE SLOVENE IN THE JANES V1.0 CORPUS (SOCIAL MEDIA) - Rolih, Maša (Slavia Centralis, 2026)
This paper explores the use of nonstandard lexis in contemporary internet Slovene based on the JANES v1.0 corpus (Fišer, Erjavec, Ljubešić 2018). It focuses on the identification and analysis of noun-based lexical items which are not included in general dictionaries, and on identifying new, contextually dependent meanings of words which are already included in dictionaries. The aim of the paper is to provide suitable lexicographic definitions for selected nonstandard expressions and to develop or, if necessary, also to complete the typology of qualifiers (Gliha Komac, Divjak Race 2022; Mikolič 2016) based on their stylistic, functional, and pragmatic use as revealed through concordance analysis. Special attention is given to the role of discourse and normative markedness. The study highlights the importance of archived corpora such as JANES v1.0 in the context of increasingly restricted access to user-generated content.
Keywords: internet Slovene; nonstandard lexis; JANES v1.0 corpora; semantics; qualifiers